2021
DOI: 10.1002/art.41584
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Intensive Acupuncture Versus Sham Acupuncture in Knee Osteoarthritis: A Randomized Controlled Trial

Abstract: Objective. To assess the efficacy of intensive acupuncture (3 times weekly for 8 weeks) versus sham acupuncture for knee osteoarthritis (OA). Methods. In this multicenter, randomized, sham-controlled trial, patients with knee OA were randomly assigned to receive electroacupuncture (EA), manual acupuncture (MA), or sham acupuncture (SA) 3 times weekly for 8 weeks. Participants, outcome assessors, and statisticians were blinded with regard to treatment group assignment. The primary outcome measure was response r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
110
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(125 citation statements)
references
References 47 publications
2
110
0
Order By: Relevance
“…For example, Tu et al assessed the efficacy of intensive acupuncture (3 times weekly for 8 weeks) versus sham acupuncture for knee osteoarthritis (KOA) in 2020, based on their previous discussion of the efficacy of acupuncture at different frequencies in the treatment of KOA. 19 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Tu et al assessed the efficacy of intensive acupuncture (3 times weekly for 8 weeks) versus sham acupuncture for knee osteoarthritis (KOA) in 2020, based on their previous discussion of the efficacy of acupuncture at different frequencies in the treatment of KOA. 19 …”
Section: Discussionmentioning
confidence: 99%
“…For example, Tu et al assessed the efficacy of intensive acupuncture (3 times weekly for 8 weeks) versus sham acupuncture for knee osteoarthritis (KOA) in 2020, based on their previous discussion of the efficacy of acupuncture at different frequencies in the treatment of KOA. 19 Through analysing the keyword, research frontiers could be identified. Consistent with previous reports, "low back pain" in the current study is the most common pain disorder that uses acupuncture as an intervention.…”
Section: Research Hotspotsmentioning
confidence: 99%
“…In their study, Tu et al showed that electroacupuncture (EA), but not manual acupuncture (MA), is superior to sham acupuncture (SA) (38 weeks) in reducing pain and improving function for patients with knee osteoarthritis (1). The trial also clearly demonstrated a potential dose effect of acupuncture.…”
Section: Who Has the Final Say On The Dose Of Acupuncture? Comment Onmentioning
confidence: 99%
“…Acupuncture is an important component of traditional Chinese medical (TCM) and an effective alternative therapy that is used to prevent and treat many diseases, including respiratory diseases. [8][9][10] Proponents argue that acupuncture is effective at relieving symptoms and improving quality of life and activity endurance, and it is associated with fewer adverse effects than conventional approaches used to treat COPD. 11 In recent years, with the increasing number of clinical studies [12][13][14] on acupuncture treatment of COPD, a certain number of systematic reviews (SRs) [15][16][17][18][19][20][21][22][23] have been published to provide corresponding evidence supporting clinical decision-making.…”
Section: Introductionmentioning
confidence: 99%